Biodegradation of PCBs by ligninolytic fungi and characterization of the degradation products - Cvančarová, Monika; Křesinová, Zdena; Filipová, Alena; Covino, Stefano; Cajthaml, Tomáš (Chemosphere, 2012)
The aim of the present study was to compare the degrading capabilities of eight ligninolytic fungal representatives towards a technical mixture of polychlorinated biphenyls (Delor 103). Axenic cultures of the fungi, either in complex or N-limited liquid media, were spiked with the technical mixture of Delor 103. All of the fungal strains were able to degrade the pollutant significantly after 6weeks of incubation in both media. Outstanding results were achieved by the treatment with Pleurotus ostreatus, which removed 98.4% and 99.6% of the PCB mixture in complex and mineral media, respectively. This fungus was the only one capable of breaking down penta- and hexachlorinated biphenyls in the complex medium. Ecotoxicological assays performed with the luminescent bacterium Vibrio fischeri demonstrated that all of the fungal strains employed in this study were able to remove the toxicity only temporarily (e.g., after 28d of incubation), while P. ostreatus was capable of suppressing the toxicity associated to PCBs along the whole incubation period in both media. We also performed an extensive set of qualitative GC/MS analyses and chlorinated derivatives of hydroxy- and methoxy-biphenyls were detected along with monoaromatic structures, i.e. chlorobenzoic acids, chlorobenzaldehydes and chlorobenzyl alcohols. This results indicate that both intracellular (cytochrome P-450 monooxigenase, aryl-alcohol dehydrogenase and aryl-aldehyde dehydrogenase) and extracellular (ligninolytic enzymes) enzymatic systems could be involved in the biotransformation of PCB by ligninolytic fungi. The data from this work also document that the fungi are able to degrade further the main metabolites on the PCB pathway (i.e. chlorobenzoic acids) simultaneously with PCBs.
Keywords: polychlorované bifenyly; houby; Pleurotus; Fungi; Biodegradation, Environmental; biodegradace; Polychlorinated Biphenyls